2018
DOI: 10.1002/jia2.25129
|View full text |Cite
|
Sign up to set email alerts
|

Cost and cost‐effectiveness analysis of pre‐exposure prophylaxis among men who have sex with men in two hospitals in Thailand

Abstract: IntroductionIn 2014, the Government of Thailand recommended pre‐exposure prophylaxis (PrEP) as an additional HIV prevention programme within Thailand's National Guidelines on HIV/AIDS Treatment Prevention. However, to date implementation and uptake of PrEP programmes have been limited, and evidence on the costs and the epidemiological and economic impact is not available.MethodsWe estimated the costs associated with PrEP provision among men having sex with men (MSM) participating in a facility‐based, prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 34 publications
3
25
0
1
Order By: Relevance
“…Novel PrEP delivery mechanisms (e.g., event-driven PrEP and long-acting PrEP injectable drugs) are being explored as alternatives to daily oral PrEP. One study in Thailand concluded that incorporating PrEP delivery into existing antiretroviral therapy programs could be a cost-effective strategy to prevent HIV infection among MSM ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel PrEP delivery mechanisms (e.g., event-driven PrEP and long-acting PrEP injectable drugs) are being explored as alternatives to daily oral PrEP. One study in Thailand concluded that incorporating PrEP delivery into existing antiretroviral therapy programs could be a cost-effective strategy to prevent HIV infection among MSM ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most governments supported PrEP programs by drafting policies and guidelines, developing or adapting PrEP training curricula, accrediting sites, and collecting and reporting data. PrEP marketing innovations, including promoting PrEP outside the typical clinical platform through drop-in centers or key population safe spaces; on social media; at meeting places such as sex clubs and gay bars; and in the community through peer outreach also were critical accelerators ( 5 ).…”
mentioning
confidence: 99%
“…74 Analyses of barriers to PrEP implementation at the systems level note that reducing financial burden related to medication is paramount for the feasibility and sustainability of PrEP programs. 75,76 In modeling studies, cost of PrEP medication is a critical factor in shortening the time horizon for the cost effectiveness of PrEP as an intervention. 24,77 And reviews of implementation efforts demonstrate that PrEP rollout is successful when government provides financial support and is impeded when such support is lacking.…”
Section: Current Guidelines For Prep Prescription and Follow-up May Bmentioning
confidence: 99%
“…Finally, Suraratcheda et al . contribute the first estimates on the costs and cost‐effectiveness of providing oral PrEP for MSM in Thailand . Costing studies related to key population programming are extremely limited yet costing data are critical for effective programme planning.…”
Section: Data Approaches To Improve Cascade Monitoringmentioning
confidence: 99%